Analisis Prediksi Kebangkrutan Pada Perusahaan Sub Sektor Hotel, Restoran Dan Pariwisata Di Bursa Efek Indonesia - Iyonna Jermina Salakay; Christina Sososutiksno; Ferry H. Basuki (CV. ITTC INDONESIA, 2026)
Financial distress is the decline stage of a company's financial condition. Companies experiencing financial difficulties in the long term have a tendency to go bankrupt. There are many people who will be harmed if a company went bankrupt, which is required for bankruptcy prediction models that can provide early warning for the company. This study was conducted to determine whether there is a difference Grover models with Altman ZScore models, Grover models with Springate models, and Grover models with Zmijewski models and to determine the most accurate bankruptcy prediction model. Research using a paired test analysis techniques samplet-test with the help of Microsoft Excel program. The conclusion of the results of this research test shows significant differences between the Grover model, the Altman Z-Score model, the Springate model, and the Zmijewski model and the most accurate of these four models is the Altman Z-Score model, because it provides very clear results in distinguishing companies that are in the safe zone and those in the warning zone.